2020
DOI: 10.5194/acp-20-14473-2020
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying bioaerosol concentrations in dust clouds through online UV-LIF and mass spectrometry measurements at the Cape Verde Atmospheric Observatory

Abstract: Abstract. Observations of the long-range transport of biological particles in the tropics via dust vectors are now seen as fundamental to the understanding of many global atmosphere–ocean biogeochemical cycles, changes in air quality, human health, ecosystem impacts, and climate. However, there is a lack of long-term measurements quantifying their presence in such conditions. Here, we present annual observations of bioaerosol concentrations based on online ultraviolet laser-induced fluorescence (UV-LIF) spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Techniques that use Ultra-violet Laser Induced Fluorescence (UV-LIF), such as the Wideband Integrated Bioaerosol Spectrometer (WIBS), provide detailed information on the size, shape and fluorescence intensity of individual particles in real time (Kaye et al, 2004). The recent investigation by Morrison et al (2020) The measurements reported here, in our current study, complement those of Morrison et al (2020) with results from locations farther down-wind than their study site of Cape Verde. Our objectives are…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Techniques that use Ultra-violet Laser Induced Fluorescence (UV-LIF), such as the Wideband Integrated Bioaerosol Spectrometer (WIBS), provide detailed information on the size, shape and fluorescence intensity of individual particles in real time (Kaye et al, 2004). The recent investigation by Morrison et al (2020) The measurements reported here, in our current study, complement those of Morrison et al (2020) with results from locations farther down-wind than their study site of Cape Verde. Our objectives are…”
Section: Introductionsupporting
confidence: 82%
“…These artifacts cannot be completely removed from the analysis but can be minimized by removing from the processing any particles whose fluorescence falls below a preset threshold. As described in the supplementary material, we follow the methodology of Perring et al, (2015) and Morrison et al (2020) by creating daily frequency histograms of the FL1, FL2 and FL3 type FAPs and use a threshold that is the mode of the frequency distribution plus nine standard deviations (9 σ) as the minimum threshold that has to be exceeded before a fluorescing event is accepted as valid. The aforementioned uncertainty due to electronic deadtime is associated with the eight milliseconds that is required to recharge after each Xenon lamp flash.…”
Section: Principles Of Operation Uncertainties and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, FBAP may also contain non-PBAP (e.g., mineral dust particles, secondary organic aerosol particles) that contribute to fluorescence (Bones et al, 2010;Lee et al, 2013;Morrison et al, 2020). The number fractions of FBAP to the total aerosol particles in the super-micron size range could be relatively similar to those of PBAP under dry conditions (Tobo et al, 2013).…”
Section: Atmospheric Cycle Of Inp-relevant Aerosolsmentioning
confidence: 99%
“…It is important to consider potential non-biological interferents in the context of these results. Previous studies have shown that dust contributes a substantial fraction of fluorescent particle loadings in remote environments (Crawford et al, 2016;D. Morrison et al, 2020).…”
Section: The Potential Effects Of Interferencesmentioning
confidence: 99%